The Effect of Sand Composition in Andosol Toward Growth and Productivity of White Maize (Zea Mays cv. Anoman) - Nikholas Hudiono - Nim: 11414030 , Adrian
Maize is one of alternative sources for carbohydrates in Indonesia. However, the cultivation system of white maize in Java region relies more on conventional methods. Ultimately, the production does not reached potential value. Development of new planting methods in limited land with alternative planting media composition can reduce land use. Determination of the optimal composition of sand with soil is expected to have production equal to the potential productivity. This study was designed to determine the effect of sand in the growth and production of white maize as well as deciding the most optimum composition for white maize cultivation. The experiment was conducted using Randomized Block Design (RBD) with 5 composition treatment (sand 0%, 10%, 30%, 50% and 70% v / v) and 5 replications. Parameters observed in maize included plant height, dry weight of root, green forage and whole corn while the planting medium parameters include C: N ratio, fill weight, porosity, moisture content, mineral and soil organic content. Sand increases the weight of the bulk density and soil porosity but decreases the capacity of the field and the production of corn crops. The most optimum medium is 90% andosol and 10% sand treatment with plant height of 175.2 cm; whole corn dry weight of 104.67 grams; forage dry weight of 88.67 grams; and root dry weight of 14.16 grams.